2002
DOI: 10.1152/ajpheart.00968.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the normal cardiac myofiber field in goat measured with MR-diffusion tensor imaging

Abstract: Cardiac myofiber orientation is a crucial determinant of the distribution of myocardial wall stress. Myofiber orientation is commonly quantified by helix and transverse angles. Accuracy of reported helix angles is limited. Reported transverse angle data are incomplete. We measured cardiac myofiber orientation postmortem in five healthy goat hearts using magnetic resonance-diffusion tensor imaging. A novel local wall-bound coordinate system was derived from the characteristics of the fiber field. The transmural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
173
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 26 publications
20
173
3
1
Order By: Relevance
“…Our mean value for the three combined hearts of FA = 0.25 ± 0.09 is similar to measurements from other studies, with values of 0.36 in canine [29], 0.35 in goat [23], 0.27 in mouse [41], and 0.36, 0.32 and 0.3 in diastolic, early and late systolic rat respectively [11] having been reported. Thus, fibre direction in the three hearts was well determined.…”
Section: Ventricular Geometrysupporting
confidence: 91%
See 2 more Smart Citations
“…Our mean value for the three combined hearts of FA = 0.25 ± 0.09 is similar to measurements from other studies, with values of 0.36 in canine [29], 0.35 in goat [23], 0.27 in mouse [41], and 0.36, 0.32 and 0.3 in diastolic, early and late systolic rat respectively [11] having been reported. Thus, fibre direction in the three hearts was well determined.…”
Section: Ventricular Geometrysupporting
confidence: 91%
“…Thus, data from different hearts were aligned at the midwall where h = 0, and the centroid for each slice is at h = −1. This normalisation method removes errors associated with identifying the locations of the endocardial and epicardial surfaces and has been validated by Geerts et al [23], who showed that the standard deviation of the inclination angle data was much reduced when compared to the usual endocardial-to-epicardial normalisation method.…”
Section: Normalised Transmural Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrous nature of the heart has been known for centuries, tracing back to as early as 1694 [28], but has been limited to tedious histological studies [20]. The cardiac fiber structure can now be imaged with diffusion tensor magnetic resonance imaging (DT-MRI) [2,15], however the variability of the fiber structure in humans is still not well known (due to the very limited number and the value of post-mortem healthy human hearts) and is largely speculated from studies on other species (dogs [12,13,11,26,22,21,9], goats [8], and rats [3]). Recently, Lombaert et al [17,18] constructed a statistical atlas of the human cardiac fiber architecture and assessed its variability.…”
Section: Introductionmentioning
confidence: 99%
“…The primary eigenvector, therefore can be used for mapping the 3D orientation of the myocardial fibres throughout the heart muscle [4]. Myocardial fibre orientation is an important determinant of myocardial wall stress [5] and exhibits a large regional and transmural variation.…”
Section: Introductionmentioning
confidence: 99%